2009
DOI: 10.1182/blood-2008-12-194852
|View full text |Cite
|
Sign up to set email alerts
|

TNFAIP3/A20 functions as a novel tumor suppressor gene in several subtypes of non-Hodgkin lymphomas

Abstract: The constitutive activation of nuclear factor-B (NF-B) has been implicated in tumorigenesis of lymphoid malignancies. We have previously shown that chromosome 6q was frequently deleted in ocular marginal zone B-cell lymphoma and identified TNFAIP3/A20, a negative regulator of NF-B pathways, as the primary target for 6q deletion. In the study reported here, we extended the analysis to other subsets of non-Hodgkin lymphomas and found that A20 is frequently deleted in mantle cell lymphoma and diffuse large B-cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
210
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 274 publications
(221 citation statements)
references
References 38 publications
10
210
1
Order By: Relevance
“…[1][2][3][4][5][6][7] In addition to A20, several NF-kB positive regulators, including CARD11, MYD88 and CD79 are frequently activated by mutation in ABC-DLBCL. [8][9][10] Our recent study also showed frequent inactivation of ABIN1, a critical adaptor molecule of the A20 inhibitory complex, in gastrointestinal DLBCL.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] In addition to A20, several NF-kB positive regulators, including CARD11, MYD88 and CD79 are frequently activated by mutation in ABC-DLBCL. [8][9][10] Our recent study also showed frequent inactivation of ABIN1, a critical adaptor molecule of the A20 inhibitory complex, in gastrointestinal DLBCL.…”
Section: Introductionmentioning
confidence: 99%
“…The generation of mutant mice deficient in CYLD has confirmed the tumor-suppressor role of this DUB because of its ability to enhance NK-kB activity (Zhang et al, 2006b). In the case of A20, chromosomal deletions and inactivating mutations have been found in several lymphoma subtypes (Honma et al, 2009;Novak et al, 2009), whereas point mutations and deletions in BAP1 have been described in breast and lung cancer (Jensen et al, 1998;Harbour et al, 2010). Furthermore, BAP1-inactivating mutations have been identified in 84% of metastasizing uveal melanomas (Harbour et al, 2010) and in 23% of malignant pleural mesotheliomas (Bott et al, 2011).…”
Section: Genetic or Functional Alterations Of Dubs In Cancermentioning
confidence: 99%
“…This could be the case of UCHL1, in which silencing by promoter methylation has been observed in some cancer cell lines and primary tumors (Yu et al, 2008). Moreover, A20 is also inactivated by promoter methylation in several lymphomas (Honma et al, 2009). Another interesting approach in this regard is the use of exogenous compounds with the ability to compensate the loss of function of tumor-suppressor DUBs inactivated in cancer.…”
Section: Targeting Dubs In Cancermentioning
confidence: 99%
“…14,27 The inhibitor of NFkB TNFAIP3/A20 was initially identified as the target of the 6q23 deletions found in ocular MZL by array-CGH. 28 Inactivating mutations of this gene were subsequently found in other lymphomas carrying 6q23 deletions including ABC-DLBCL, MCL, and Hodgkin's lymphoma (HL). 28,29 Inactivating mutations of PRDM1/BLIMP1 occur in DLBCL with deletions of 6q21.…”
Section: Platformsmentioning
confidence: 99%
“…28 Inactivating mutations of this gene were subsequently found in other lymphomas carrying 6q23 deletions including ABC-DLBCL, MCL, and Hodgkin's lymphoma (HL). 28,29 Inactivating mutations of PRDM1/BLIMP1 occur in DLBCL with deletions of 6q21. A recent combined CGH array and gene expression profiling study of NK-cell neoplasms has also recognized 6q21 deletions and inactivating PRDM1 mutations in these tumors.…”
Section: Platformsmentioning
confidence: 99%